Dynamical model of the vocal tract in consonant and nasalized articulation - NOWAKOWSKA, Wanda; ŻARNECKI, Piotr (Archives of Acoustics, 1989)
In the paper a simulation model of the vocal organ is presented. The model has been programmed in Turbo Pascal for an IBM PC computer. With the use of this model as a research tool the possibilities of analysing the formant structure of the speech signal has been demonstrated in the static states for the cases of oral and nasalized vowels and nasal consonants. For analysed speech sounds the approximate vocal tract cross-sections were determined. An example of simulation of continuous changes of the articulatory tract geometry which take place in natural speech has been presented and the accompanying changes of the phonetical and acoustical structure of the signal has been described. Also potential possibilities of applying the described model to the studies on the phenomenons of coarticulation and articulation in the conditions of forced nasalization has been demonstrated.